Digital Innovation Through Sharialearn to Enhance Students’s Literacy in Islamic Banking - Arthur Vogal Pramudya; Verbena Ayuningsih Purbasari (Universitas Islam Negeri (UIN) Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: This study aims to develop the ShariaLearn educational application and analyze its effectiveness in improving students’ Islamic banking literacy. Research Methods: This study employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through expert validation as well as pre-test and post-test results from students of MAN 1 Ngawi, which were then analyzed using a paired sample t-test. Results: The findings indicate that ShariaLearn was successfully developed by providing comprehensive materials on the principles, contracts, and products of Islamic banking. Empirical findings confirmed a significant difference between pre-test and post-test scores, indicating that the use of interactive digital media can overcome students’ low contextual understanding. Conclusion: The ShariaLearn application is effective as an independent learning medium. Its implication is that the integration of technology into school curricula can accelerate the improvement of Islamic financial literacy among the younger generation.